Method for preparing plasmid DNA - Mohamed, Farahidah; Doolaanea, Abd Almonem; Mansor, Nur 'Izzati (2015)
A METHOD FOR PREPARING PLASMID DNA, COMPRISING THE STEPS OF CULTURING HOST CELLS CONTAINING PLASMID DNA; LYSING THE HOST CELLS TO OBTAIN A LYSATE; ISOLATING SAID PLASMID DNA FROM SAID LYSATE TO FORM ISOLATED PLASMID DNA; AND PURIFYING THE ISOLATED PLASMID DNA; CHARACTERIZED IN THAT THE LYSATE IS SUBSTANTIALLY LYOPHILIZED AND SUBSEQUENTLY RESUSPENDED WITH WATER, PRIOR TO ISOLATION. (FIG 5A)